Drug interactions in HIV-infected patients treated for hepatitis C. (3rd August 2017) - Soriano, Vicente; Labarga, Pablo; Fernandez-Montero, José V.; Mendoza, Carmen de; Benítez-Gutiérrez, Laura; Peña, José M.; Barreiro, Pablo
ABSTRACT: Introduction : The introduction of direct-acting antivirals (DAA) has revolutionized the hepatitis C field. Most hepatitis C patients can now be cured, including those coinfected with HIV. However, drug-drug interactions (DDI) between DAA and antiretrovirals (ARV) should be known to prevent either toxicity due to drug overexposure or treatment failures due to low drug concentrations. Areas covered : Clinically significant DDI may be classified as major (when co-administration should be contraindicated) or minor (when they require close monitoring, changes in drug dosage or in timing). Strategies for preventing and managing DDI influence response rates in HIV/HCV-coinfected patients. Pharmacokinetic evidence of interactions from clinical trials and reports from real-world experience are discussed. Expert opinion : The most frequent DDI between DAA and ARV affect drug metabolism by CYP450 induction/inhibition, leading to abnormal drug exposures. Throughout this mechanism interact HCV and HIV boosted protease inhibitors, and most non-nucleoside HCV and HIV polymerase inhibitors. In contrast, HIV and HCV nucleos(t)ide analogue polymerase inhibitors, most HCV NS5A inhibitors and HIV integrase inhibitors (e.g., dolutegravir), do not or only marginally affect CYP450, and therefore are relatively free of DDI. Exposure to some HIV and HCV nucleos(t)ide analogues (e.g., tenofovir and sofosbuvir, respectively) is subject to induction/inhibition of drug transporters (e.g., P-glycoprotein) and requires special attention in patients with renal insufficiency.